Uma Leitura do Culto Contemporâneo ao Corpo - FONTES, Malu (Contemporanea : Revista de Comunicação e Cultura, 2006)
This article discusses the social and aesthetic processes of (re)signiﬁcation of the body throughout the twentieth century, and the body form considered canonical at the end of that period. The canonical body inherited by the twenty-ﬁrst century is characterized by display in the mass media, as illustrated by the way the female body is idealized, submitted to beautifying techniques and practices that transform appearance and anatomy. This article discusses the social, historical and cultural context from which the cult of physical ﬁtness and the building of the contemporary canonical body emerged.